Exploiting Enhanced Altimetry for Constraining Mesoscale Variability in the Nordic Seas and Arctic Ocean - Antonio Bonaduce; Andrea Storto; Andrea Cipollone; Roshin P. Raj; Chunxue Yang (Remote Sensing)
Recent advances in Arctic observational capabilities have revealed that the Arctic Ocean is highly turbulent in all seasons and have improved temporal and spatial sampling of sea level retrievals from remote sensing, even above 80°N. Such data are expected to be increasingly valuable in the future when the extent of sea ice in the Arctic Ocean is reduced. Assimilating this new data into ocean models, together with in situ observations, provides an enriched representation of the mesoscale population that induces new eddy-driven contributions to local dynamics and thermodynamics. To quantify the content of the new information, we compare three-year-long assimilative experiments at ¼° resolution incorporating in situ-only data, in situ and standard altimetry, and in situ and high-latitude-enhanced altimetry, respectively. The enhanced altimetry data lead to an increase in three-dimensional eddy kinetic energy, generated by coherent vortexes, of up to 20% in several areas. Robust ocean warming is generated in the Arctic sector down to 800 m. Via heat budget analysis, this warming can be ascribed to a local enhancement of vertical mixing, as well as an increase in meridional heat transport. The assimilation of enhanced altimetry amplifies the transport, compared to standard altimetry, especially north of 70°N.